The antiproliferative and antioxidant activities of the essential oils of Juniperus species from Turkey. (2nd June 2020) - Sahin Yaglioglu, Ayse; Eser, Ferda; Yaglioglu, Muhammet Samil; Demirtas, Ibrahim
Abstract: The present study aimed to determine the essential oil compositions of four different types of Juniperus species including Juniperus oxycedrus ssp oxycedrus L., Juniperus foetidissima Willd., Juniperus excelsa M. Bieb, and Juniperus communis L. with their antioxidant and antiproliferative activities. The antiproliferative activity of the essential oils was determined against HeLa (human cervix carcinoma) and C6 (rat brain tumor cell) cell lines by BrdU cell proliferation assay. The essential oils were tested for their total reducing power activity, DPPH (2, 2'‐diphenyl‐1‐picrylhydrazyl) free radical scavenging activities, and hydrogen peroxide scavenging activities. The overall results of the study showed that the needles of Juniperus species have strong antiproliferative activities as cell selective against C6 cells. Abstract : Antiproliferative and antioxidant activities of essential oils of Juniperus species.